The 7Li(18O, 17O)8Li reaction and the 17O + 8Li potential - O. A. Bezshyyko; A. N. Vodin; L. O. Golinka-Bezshyyko; A. N. Dovbnya; I. M. Kadenko; O. A. Kovalenko; V. A. Kushnir; A. I. Levon; V. V. Mitrochenko; S. N. Olejnik; G. E. Tuller (Âderna Fìzika ta Energetika, 2009)
This paper deals with the results of isomer ratio measurements for nuclei 110m,gIn and 108m,gIn from photonuclear reactions 113In(γ, 3n)110m,gIn, 115In(γ, 5n)110m,gIn, 115In(γ, 7n)108m,gIn. Bremsstrahlung energies varied within (34÷43) MeV for 113In(γ, 3n)110m,gIn reaction, in energy region (43÷100) MeV for 115In(γ, 5n)110m,gIn and 115In(γ, 7n)108m,gIn reactions. The instrumental gamma-ray spectra of irradiated target specimens have been measured with high purity germanium semiconductor spectrometer. The isomer ratio results and dependence of isomer ratios upon maximal bremsstrahlung energies within selected range are obtained and discussed.